GLOBAL QUANTITY DIFFERENCES IN MOTOR ABILITIES OF PRE-SCHOOL BOYS - Dževad Džibrić,; Tarik Huremović,; Damir Ahmić, (Sport Scientific And Practical Aspects, 2025)
Based on the sample of 58 male respondents (30 respondents were a part of experimental group and 28 of control group) age from five to five and a half years old, initial and final measuring was conducted with the aim to determine global quantitative changes in motor abilities between these two groups. Experimental group carried out specially designed physical education program suitable for pre-school children that lasted for three days, weekly totally 60 minutes in the Gym managed by physical education professor, while control group followed current program for pre-school education in the classroom (playground) managed by kindergarten teacher. Possible differences were determined between experimental and control group in initial and final measuring in a period of three months participation in physical education program To test motor abilities we applied 6 tests. We applied canonic discriminative analysis to determine global quantitative differences between these two groups in the area of motor abilities. Obtained results indicate there are no differences between groups in initial measuring, but in final measuring we noticed statistically significant differences regarding experimental group which means there has been some positive transformations in motor abilities of this group. Possible reason lies in program organized for experimental group as well as different approach to realization of treatment and material working conditions where the classes were carried out.